Assessing the water quality impacts of two Category-5 hurricanes on St. Thomas, Virgin Islands. (15th March 2020) - Jiang, Sunny C.; Han, Muyue; Chandrasekaran, Srikiran; Fang, Yingcong; Kellogg, Christina A.
Abstract: Managing waterborne and water-related diseases is one of the most critical factors in the aftermath of hurricane-induced natural disasters. The goal of the study was to identify water-quality impairments in order to set the priorities for post-hurricane relief and to guide future decisions on disaster preparation and relief administration. Field investigations were carried out on St. Thomas, U.S. Virgin Islands as soon as the disaster area became accessible after the back-to-back hurricane strikes by Irma and Maria in 2017. Water samples were collected from individual household rain cisterns, the coastal ocean, and street-surface runoffs for microbial concentration. The microbial community structure and the occurrence of potential human pathogens were investigated in samples using next generation sequencing. Loop mediated isothermal amplification was employed to detect fecal indicator bacteria, Enterococcus faecalis . The results showed both fecal indicator bacteria and Legionella genetic markers were prevalent but were low in concentration in the water samples. Among the 22 cistern samples, 86% were positive for Legionella and 82% for Escherichia-Shigella . Enterococcus faecalis was detected in over 68% of the rain cisterns and in 60% of the coastal waters (n = 20). Microbial community composition in coastal water samples was significantly different from cistern water and runoff water. Although identification at bacterial genus level is not direct evidence of human pathogens, our results suggest cistern water quality needs more organized attention for protection of human health, and that preparation and prevention measures should be taken before natural disasters strike. Graphical abstract: Image 1 Highlights: Rain cistern, coastal ocean and surface runoff waters were sampled post hurricanes. Microbial community composition was dramatically different in each type of water. Fecal indicator bacteria and Legionella were prevalent in all water samples. The concentrations of Legionella and fecal indicator bacteria were generally low.